PENGARUH DISIPLIN KERJA, KEPEMIMPINAN, DAN PENGAWASAN TERHADAP KINERJA KARYAWAN PADA PT BANK SYARIAH INDONESIA KC BATURAJA RAHMAN HAMIDI - Darman Syafei; Maulana Hadi Kusuma; Muznah Muznah; Putri Yulanda (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2023)
ABSTRACT This research discussed the influence of work discipline, leadership and supervision on employees' performance at PT Bank Syariah Indonesia KC Baturaja Rahman Hamidi. The analytical method used was a quantitative method using multiple linear regression analysis tools. The results of the analysis explained the t count of each Work Discipline variable (X1) of 2.243 Leadership (X2) of 3.486 Supervision (X3) of 2.726 which was greater than t table of 2.05954 which stated that all variables had a significant influence on Employees' Performance at PT Bank Syariah Indonesia KC Baturaja Rahman Hamidi. The calculated F value of 9.013 was greater than 2.99 which stated that work discipline, leadership, and supervision had a significant influence on employees'performance at PT Bank Syariah Indonesia KC Baturaja Rahman Hamidi. The value of the coefficient of determination (adjusted R square) of 0.462 meant that in this case the contribution of employee influence was 46.2% and the remaining 53.8% was influenced by other variables not mentioned in this study such as work ability, motivation, competence, work facilities, and work culture (Afandi, 2021:86).